-9x-1=-5x+3

Simple and best practice solution for -9x-1=-5x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x-1=-5x+3 equation:


Simplifying
-9x + -1 = -5x + 3

Reorder the terms:
-1 + -9x = -5x + 3

Reorder the terms:
-1 + -9x = 3 + -5x

Solving
-1 + -9x = 3 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-1 + -9x + 5x = 3 + -5x + 5x

Combine like terms: -9x + 5x = -4x
-1 + -4x = 3 + -5x + 5x

Combine like terms: -5x + 5x = 0
-1 + -4x = 3 + 0
-1 + -4x = 3

Add '1' to each side of the equation.
-1 + 1 + -4x = 3 + 1

Combine like terms: -1 + 1 = 0
0 + -4x = 3 + 1
-4x = 3 + 1

Combine like terms: 3 + 1 = 4
-4x = 4

Divide each side by '-4'.
x = -1

Simplifying
x = -1

See similar equations:

| -7x+11=-3x+19 | | -5x+11=-x-25 | | -3x-17=-14 | | 6x+14=3x+2 | | 13x+22=6x+71 | | 7x+18=4x+48 | | 2x+21=x+20 | | 8(t-3)+7t=5(3t+3)-10 | | 2y+3y=0 | | -5x-1=-x+19 | | 1x+3x=17500 | | 11x-13=4x+29 | | 2x^2+3y^2-2x+6y-7=0 | | 2t-8=-7+3t | | 209.04=0.85x50x0.325x0.7xDx(0.753-((0.7xD)/2) | | 4t+11=-8+t | | 2x=1505.94 | | 6(n-3)+5=2n+5 | | 2x+5=23 | | 35x+(20y)3=17500 | | 13+6x=43 | | 41/8x5 | | 8cos^3(x)-6cos(x)=1 | | 35x+(20y*3)=17500 | | 8d+2=4d+3 | | 35x+(20x*3)=17500 | | 35x+60y=17500 | | 35x+60y=120 | | 3x+(2x)2=12 | | x/1.12*0.06x=121,480 | | 8n-9=6+3n | | x/1.12*0.06x |

Equations solver categories